Indexing and visibility of the Peruvian Journal of Health Sciences of the University of Huanuco. - Ubillús, Milward (2022)
The indexing of the Peruvian Journal of Health Sciences of the University of Huanuco (UDH) in Latindex-Regional Online Information System for Scientific Journals of Latin America, the Caribbean, Spain and Portugal, represents an academic achievement of this house of studies and its editorial team. But that is not all because, in addition to being an official organ of academic publications, it becomes an opportunity for local and national health sciences researchers to present their work and research to the national and international scientific community, with due compliance with the minimum requirements demanded today by globalization and scientific knowledge, in addition to promoting the increase of individual production of teachers of health sciences careers, so that they can access the category of CONCYTEC researchers in Peru and the stimuli of scientific publication.